(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the theoretical and methodological foundations of scientific research in tourism activities. It outlines the main theoretical frameworks used in tourism studies, including systems theory, motivation theory, and sustainable development concepts. The paper explores various research methodologies—quantitative, qualitative, and mixed methods—emphasizing their role in producing reliable and applicable knowledge. The interdisciplinary nature of tourism research, the use of digital technologies, ethical considerations, and post-pandemic research trends are also discussed. The article aims to provide scholars and practitioners with a comprehensive understanding of how scientific research can contribute to sustainable and informed tourism development.